1995
DOI: 10.1182/blood.v85.12.3412.bloodjournal85123412
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of early hematopoietic progenitor cells with BB-10010: a genetically engineered variant of human macrophage inflammatory protein- 1 alpha

Abstract: is a genetically engineered variant of human macrophage inflammatory protein-la with improved solution properties. We show here that it mobilizes stem cells into the peripheral blood. We investigated the mobilizing effects of 88-10010 on the numbers of circulating 8-day spleen colony-forming units (CFU-S8), CFU-S,2, and progenitors with marrow repopulating ability (MM). A single subcutaneous dose of 88-10010 caused a twofold increase in circulating numbers of CFU-SI, CFU-S12, and M M 30 minutes after dosing. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(44 citation statements)
references
References 5 publications
5
36
0
Order By: Relevance
“…In the mouse system it is clear that the spleen has an important role in the control of the peripheral blood cell population after denervation, as has been seen with cytokine-stimulated progenitor cell mobilization and leucocyte numbers (Molineux et al, 1990a, b;Lord et al, 1995) and as has been reported in humans after splenectomy (McBride et al, 1968). In our experiments, as in those reported by others, splenectomy apparently unmasks the full extent of peripheral blood mobilization of progenitor cells.…”
Section: Discussionsupporting
confidence: 86%
“…In the mouse system it is clear that the spleen has an important role in the control of the peripheral blood cell population after denervation, as has been seen with cytokine-stimulated progenitor cell mobilization and leucocyte numbers (Molineux et al, 1990a, b;Lord et al, 1995) and as has been reported in humans after splenectomy (McBride et al, 1968). In our experiments, as in those reported by others, splenectomy apparently unmasks the full extent of peripheral blood mobilization of progenitor cells.…”
Section: Discussionsupporting
confidence: 86%
“…MIP-1␣/CCL3 was one of the first members of the chemokine family to be used to mobilize HPCs and HSCs to the blood of mice. 30 This mobilization is mediated through chemokine receptor CCR1, 32 which is one of the receptors that bind MIP-1␣. Mobilization of HPCs in mice with MIP-1␣/CCL3 is potent and rapid, with maximal effects occurring within 1 h. We reasoned that mobilization with MIP-1␣/CCL3 might be different in mechanism than that of AMD3100, which works through antagonizing the binding of SDF-1/CXCL12 to its receptor, CXCR4, 14 and also that of G-CSF, which occurs as a much more prolonged response after days of multiple administrations of G-CSF.…”
Section: Effect Of Mip-1␣/ccl3 On the Mobilization Of Hpcs Alone Andmentioning
confidence: 99%
“…Murine HSC capable of reconstituting a myeloablated animal can be harvested from cytokine mobilized peripheral blood in much the same way as in humans (Molineux et al, 1990). Briddell et al (1993) Georges et al, 1998) Mobilizing regimen Reference G-CSF Briddell et al (1993) Cyclophosphamide Neben et al (1993) Stem cell factor (SCG) Mauch et al (1995) Stem cell factor + G-CSF Briddell et al (1993) IL-1β Fibbe et al (1992) IL-6 Suzuki et al (1995) IL-6 + G-CSF Suzuki et al (1995) IL-7 Grzegorzewski et al (1995) IL-8 Laterveer et al (1995) IL-11 Mauch et al (1995) IL-11 + SCF Mauch et al (1995) FLT-3 + G-CSF Sudo et al (1997) MIP-1α Lord et al (1995) MIP-1α + G-CSF Lord et al (1995) mice transplanted with 500,000 donor G-CSFmobilized peripheral-blood low-density cells. Donor mice received seven daily injections of human G-CSF at a dose of 200 µg/kg.…”
Section: Mobilized Peripheral Bloodmentioning
confidence: 99%